ผลของโปรแกรม EF GUIDELINE ต่อทักษะการคิดเชิงบริหาร: การศึกษาติดตามผล เด็กปฐมวัยในห้องเรียนที่ใช้แผนการจัดประสบการณ์ตามแนวทาง EF GUIDELINE ในพื้นที่กรุงเทพมหานคร THE IMPACTS OF THE EF GUIDELINE PROGRAM ON EXECUTIVE FUNCTION SKILLS: A FOLLOW–UP STUDY OF CH - โพธยานุกูล วรวลัญช์; ธนเศรษฐกร ปนัดดา; เสรี พัชรินทร์; เจี่ยวิวรรธน์กุล อธิวัฒน์ (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ ในปี พ.ศ. 2560 สำนักงานกองทุนสนับสนุนการสร้างเสริมสุขภาพ ได้สนับสนุนให้สถาบันแห่งชาติเพื่อการพัฒนาเด็กและครอบครัว, มหาวิทยาลัยมหิดล และ สถาบันรักลูก ดำเนินการวิจัยและพัฒนา EF Guideline ซึ่งเป็นเครื่องมือสำหรับครูปฐมวัย ใช้เป็นแนวทางในการวางแผนการจัดประสบการณ์ และสภาพแวดล้อม เพื่อส่งเสริมทักษะการคิดเชิงบริหารของเด็กปฐมวัย ในโครงการวิจัยปฏิบัติการเชิงวิพากษ์ หลังจากที่ครูปฐมวัยนำ EF Guideline ไปใช้เป็นเวลาหนึ่งภาคเรียน (4 เดือน) ผลการวิจัยพบว่า ทักษะการสอนของครู จากการใช้แผนการจัดประสบการณ์ EF Guideline และ ทักษะการคิดเชิงบริหารในเด็กปฐมวัยมีการเปลี่ยนแปลงดีขึ้นอย่างมีนัยยะสำคัญทางสถิติ (ปนัดดา ธนเศรษฐกร และคณะ, 2560) งานวิจัยชิ้นนี้จึงมีวัตถุประสงค์ คือ (1) เพื่อติดตามความคงอยู่ของการเปลี่ยนแปลงความรู้ ทักษะและทัศนคติของการใช้แผนการจัดประสบการณ์ EF Guideline ในคุณครูปฐมวัยในภาคเรียนที่ 2 และ (2) เพื่อติดตามพัฒนาการทักษะการคิดเชิงบริหารของเด็กปฐมวัยในภาคเรียนที่ 2 ในห้องเรียนที่ใช้แผนการจัดประสบการณ์ตามแนวทาง EF Guideline ในเขตกรุงเทพมหานคร โดยใช้ระเบียบวิธีการวิจัยแบบผสมผสาน กลุ่มตัวอย่างคือ คุณครูและเด็กปฐมวัย ภาคเรียนที่ 1/2560 จำนวน 4 โรงเรียนในกรุงเทพมหานคร แบ่งเป็น (1) คุณครูที่ผ่านการอบรมการจัดประสบการณ์ EF Guideline จำนวน 7 คน และ(2) เด็กปฐมวัยในห้องเรียนที่ได้รับการจัดประสบการณ์ตามแนวทาง EF Guideline จำนวน 134 คน ผลการศึกษาพบว่า หลังจากจบโครงการ EF Guideline Training Program ในภาคเรียนที่ 1 คุณครูที่เข้าร่วมโครงการยังคงวางแผนการจัดประสบการณ์ และจัดกิจกรรมตามแนวทาง EF Guideline ในภาคเรียนที่ 2 และคาดว่าจะใช้ต่อเนื่องไป เนื่องจากคุณครูตระหนักเห็นคุณค่าของการเขียนแผนการจัดประสบการณ์ที่มีเป้าหมาย และมีวัตถุประสงค์ชัดเจน ซึ่งทำให้เกิดความประณีตและละเอียดถี่ถ้วนต่อการสร้างประสบการณ์ในเด็กปฐมวัย และยังมีส่วนช่วยให้คุณครูเขียนแผนการจัดประสบการณ์ได้ง่ายขึ้น นอกจากนี้เด็กปฐมวัยในห้องเรียนที่คุณครูใช้ EF Guideline ทั้งฉบับเป็นแนวทาง ในการจัดประสบการณ์การเรียนรู้อย่างต่อเนื่อง มีค่าเฉลี่ยคะแนนทักษะความคิดเชิงบริหารในภาคเรียนที่ 2 สูงกว่าภาคเรียนที่ 1 อย่างมีนัยสำคัญทางสถิติ ที่ระดับ p < .05 คำสำคัญ: ทักษะการคิดเชิงบริหาร โปรแกรมส่งเสริมทักษะการคิดเชิงบริหาร เด็กปฐมวัย ABSTRACT In 2017, EF Guideline, the teacher tool for planning learning experiences and environments for promoting kindergarten children’s executive function (EF) skills, was developed and studied by the collaboration between National Institute for Child and Family Development, Mahidol University and RLG Institute and funded by Thai Health Promotion Foundation to investigate the impact of the EF Guideline program on teachers’ teaching skills and children’s EF skills. After implementing for one semester (4 months), the findings showed that both teaching skills and children’s EF skills were significantly improved. In this research, the follow – up of children in the classrooms where lesson plans based on EF Guideline was focused. The objectives of the study were (1) to follow – up the persistence of the teachers’ changes in their teaching practices; including knowledge, attitude, and skills in semester 2, and (2) to investigate the development of children’s EF skills in semester 2. A mixed method research was designed to answer the research questions. Four kindergarten schools in Bangkok containing 7 teachers who participated in the EF Guideline program and implementing learning experiences based on EF Guideline in semester I and their 134 children were purposively selected to be the sample. The instruments were the interview questions of EF Guideline Persistence and the Assessment of Executive Function in Early Childhood (MU.EF - 101). For the data analysis, constant comparative analysis using themes and interpretive description was utilized to explain the persistence of the EF Guideline program in the classrooms. Moreover, paired t - test was utilized to evaluate the differences in the children’s scores on the development of EF skills between the semester 1 and semester 2. The results from the constant comparative analysis yielded 3 themes, including EF Guideline Principles and Components (Knowledge), The Behavioral Changes in Mutual Interactions (Attitude), and Teaching Skills (Practice). The results also showed that the children in the classroom where their teachers had continuously used the full form of the EF Guideline had significantly higher scores on the development of EF skills in semester 2, comparing to their scores in the semester 1. The depth of knowledge, attitude, and the consistency of the mechanism of EF Guideline element were the significant results. Thus, EF Guideline training program was developed to increase the teacher’s competence since it impacts the children’s EF skills. Keyword: Executive function skills, EF Skills, Program, Preschool, EF Guideline